The effect of NF-κB antisense oligonucleotide on transdifferentiation of fibroblast in lung tissue of mice injured by bleomycin - Zhou, Yan (Springer Netherlands, 2014)
To investigate the influence of NF-κB antisense oligonucleotide on transdifferentiation of fibroblast in the pathological process of bleomycin-induced pulmonary fibrosis in mice. 6 h before molding of C57BL/6 model of pulmonary fibrosis in mice, NF-κB antisense oligonucleotide was injected from caudal vein. Then the lung tissue was collected for primary culture as well as model group and control group. Cultured cells were used for immunocytochemical staining of p65, IκB-α and α-SMA proteins as well as in situ hybridization staining of p65 and IκB-α. Then image analysis was carried out. The expressions of all the indicators were expressed as mean optical density. Compared with the control group, the expressions of p65 protein, IκB-α protein and α-SMA protein of model group were increased, as well as the expressions of p65 mRNA and IκB-α mRNA (P < 0.05). Compared with model group, the expressions of all indicators of intervention group were decreased (P < 0.05). P65 protein and p65 mRNA were positively correlated with the expression of α-SMA protein respectively. p65 protein and p65 mRNA were positively correlated with the expressions of IκB-α protein and IκB-α mRNA respectively. NF-κB antisense oligonucleotide can inhibit the transdifferentiation of fibroblast towards myofibroblast in the pathological process of bleomycin-induced pulmonary fibrosis in mice.